Implementation of ‘Aqidah Education in Nisa’iyah Subjects on the Cultivation of Akhlaq Karimah (A Case Study at Pondok Modern Darussalam Gontor Putri Campus 1) - Ihsan, Nur Hadi; Fauziyah, Afifah (Universitas Muhammadiyah Ponorogo, 2024)
This study examines the implementation of ‘aqidah education in Nisa’iyah subjects for cultivating akhlaq karimah (noble character) at Pondok Modern Darussalam Gontor Putri Campus 1. Employing a qualitative case study approach, it investigates how ‘aqidah values are integrated into Nisa’iyah subjects, which include women's fiqh, women's psychology, women's health, and women's skills. Data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that this integrative approach significantly contributes to shaping akhlaq karimah among female students, aligning with Pondok's educational objectives and contemporary societal needs. Key factors influencing this process include student motivation, socio-cultural background, and the Pondok's educational environment. The integration of ‘aqidah education is carried out through cognitive understanding, affective appreciation, and psychomotor practice, fostering a holistic development of students' character. The study underscores the pivotal role of Islamic education in nurturing Muslim women with noble character, preparing them to face modern challenges. Additionally, it highlights the necessity of continuous curriculum evaluation in response to evolving social and technological contexts. This research contributes to the discourse on Islamic education by offering a model for integrating ‘aqidah and akhlaq in a comprehensive manner. It emphasizes the importance of a balanced educational approach that addresses intellectual, emotional, and practical dimensions, ensuring that students develop into individuals with strong moral character, social responsibility, and adaptive skills required to navigate contemporary societal shifts.